2018
DOI: 10.1002/em.22227
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Pig‐a, micronucleus, and comet assay endpoints in rats treated by acute or repeated dosing protocols with procarbazine hydrochloride and ethyl carbamate

Abstract: The utility and sensitivity of the newly developed flow cytometric Pig‐a gene mutation assay have become a great concern recently. In this study, we have examined the feasibility of integrating the Pig‐a assay as well as micronucleus and Comet endpoints into acute and subchronic general toxicology studies. Male Sprague–Dawley rats were treated for 3 or 28 consecutive days by oral gavage with procarbazine hydrochloride (PCZ) or ethyl carbamate (EC) up to the maximum tolerated dose. The induction of CD59‐negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…While Phonethepswath et al () also reported PCH‐induced Pig‐a mutation in mice, it is not productive comparing those results with data reported herein because the previous study utilized an early mouse blood labeling protocol that is now understood to systematically underestimate mutant cell frequency (Labash et al ). Finally, Chen et al () recently reported strong induction of Pig‐a mutations following a 28‐day exposure regimen in rats using daily doses higher than those used here. Thus, in addition to its well‐known clastogenic activity, PCH is also an effective in vivo mutagen when recommended OECD test guideline experimental design considerations are followed.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…While Phonethepswath et al () also reported PCH‐induced Pig‐a mutation in mice, it is not productive comparing those results with data reported herein because the previous study utilized an early mouse blood labeling protocol that is now understood to systematically underestimate mutant cell frequency (Labash et al ). Finally, Chen et al () recently reported strong induction of Pig‐a mutations following a 28‐day exposure regimen in rats using daily doses higher than those used here. Thus, in addition to its well‐known clastogenic activity, PCH is also an effective in vivo mutagen when recommended OECD test guideline experimental design considerations are followed.…”
Section: Discussionmentioning
confidence: 59%
“…PCH appears to be a particularly effective in vivo clastogen inducing both micronuclei in bone marrow (Romagna and Schneider 1990) and DNA breaks as detected by the alkaline elution (Holme et al 1989) and comet (Sasaki et al 1998) assays in multiple tissues including stomach and liver. Furthermore, significant increases in median percent tail DNA were recently reported in bone marrow, liver, kidney, and lungs of rats, 1 day after a 28-day exposure to 30 or 60 mg PCH/kg/day (Chen et al 2019). However, PCH's mutagenic activity is less well-characterized.…”
Section: Introductionmentioning
confidence: 99%